TECHNOLOGIES OF PSYCHOLOGICAL HELP FOR PARENTS OF CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) IN THE HEALTH PRESERVATION ASPECT - Honcharenko, Natalia (PSYCHOLOGICAL JOURNAL, 2020)
The article is devoted to topical issues of providing professional psychological assistance in Ukraine. It is emphasized that in the conditions of social crises in the country, which take place against the background of the formation of the information society, the requirements for the quality and scientific provability of psychological technologies implemented in the work of psychological services are increasing. It is noted that the number of people suffering from various mental disorders in Ukraine is increasing, which exacerbates the issue of health care. The main aspects of the article focus on helping parents of children with attention deficit hyperactivity disorder, in particular, those psychological technologies, the introduction of which would improve the overall psychological well-being of all family members to avoid negative consequences of ADHD in children and promote its development. It is pointed out that the positive dynamics of the development of a child with ADHD is facilitated by the creation of a system of positive behavioural guidance in the family. Such favourable conditions for child development in the family are often suboptimal for parents of children with ADHD, due to the high probability of disorders in themselves, their tendency to anxiety, depression, high levels of stress. In such cases, CPT technologies (cognitive-behavioural therapy) and mindfulness practices are offered as effective means of psychological assistance to parents of children with ADHD. Examples of changes in the structure of the human brain with ADHD under the influence of CPT, which contributes to the improvement of general conditions in the symptoms of the syndrome, are empirically proven in neurological visual studies. Mindfulness techniques help to neutralise stress, increase emotional intelligence, tone, resilience, self-acceptance, quality of life in general. The mechanisms of action of mindfulness practices in anxiety, depression and stress are methodologically described on the basis of the provisions of the theory of interacting cognitive subsystems F. Bernard and S. Tizdale, through the functioning of ruminations (Z. Segal, M. William and J. Tizdale) and on the principles of theory Ukhtomsky. On the basis of theoretical analysis, a conclusion was made about the feasibility of using in programs of psychological assistance to parents of children with ADHD cognitive-behavioral therapy techniques and mindfulness practices, which are effective non-drug tools in their health and resources.